A Spectroscopic Study of the Interaction between Cyanine Dyes with Different Skeleton Structures and Transferrin. Issue 45 (4th December 2018) - Lang, Yunhe; Shi, Lei; Lan, Ling; Zhao, Zheng; Yang, Qianfan; Chen, Lei; Sun, Xiaoran; Tang, Yalin; Zhang, Xiufeng
Abstract: Human serum transferrin (hTf) has been exploited as a bio‐carrier for targeted drugs to cancer cells where transferrin receptors are expressed at high levels. In this study, cyanine dyes DMSA and DMSB with a similar main core structure were selected to evaluate the effects of heterocycle on binding with hTf by spectroscopic methods. Fluorescence spectral results have shown that DMSB, which contains a selenazole ring, had a strong affinity binding with transferrin, up to 10 4 ‐fold higher than DMSA, which contains a thiazole ring. This difference may be attributed to the larger molecular volume of selenazole compared with DMSA. Binding distance between cyanine dyes and hTf demonstrated that the non‐radioactive energy transfer mechanism was also involved in the fluorescence quenching of protein. Furthermore, DMSB‐binding gave rise to a greater decrease of the α‐helix content of hTf than DMSA suggesting that hTf, which shows a looser structure binding with DMSB, increased polarity around the tryptophan residues of hTf, which was confirmed by circular dichroism and synchronous fluorescence spectroscopy. The study provides a certain theoretical basis for the design of cyanine dyes as biomolecular probe to target drugs for hTf. Abstract : Compare the interaction of cyanine dye DMSA and DMSB binding with human serum transferrin through spectroscopic methods. The studies suggest that DMSB with selenazole ring bound with hTf had a higher affinity almost 10 4 ‐fold than that of DMSA with thiazole ring. Besides, DMSB gave rise to a greater conformation changes of hTf than DMSA, indicating DMSB had outstanding performance binding with hTf. This in vitro method has the potential to become a rapid tool for the confirmation of protein‐biomolecule interactions.